(untitled) (Web of Teachers: Inderscience Research, 2024)
Innovative teaching strategies are instructional approaches that involve the use of technology, hands-on activities, and other materials to help students learn in a meaningful way. These strategies focus on engaging students and encouraging them to take an active role in their learning. Innovative teaching strategies are instructional approaches that involve the use of technology, hands-on activities, and other materials to help students learn in a meaningful way. These strategies focus on engaging students and encouraging them to take an active role in their learning. Innovative teaching strategies are beneficial because they create a more engaging learning environment. By providing various ways for students to interact with the material, these strategies can help them gain a deeper understanding of the subject matter. When students have the opportunity to explore, think critically, and collaborate, they can develop their problem-solving and decision-making skills. These strategies can help foster collaboration among students, as they are given the opportunity to work together to solve problems.